EFEKTIVITAS KOMPRES JAHE MERAH TERHADAP NYERI SENDI PENDERITA REUMATHOID ARTRITIS - Mujahidin (Jurnal Kesehatan dan Pembangunan, 2023)
One of the health problems that occurs quite a lot in the community, one of which is rheumatoid arthritis or often referred to by the community as rheumatic disease. Rheumatoid arthritis is most often found in the age range of 50 to 60 years, this reinforces the assumption that this disease is indeed a type of disease that is quite closely related to degenerative processes. Someone who suffers from this disease will feel a typical complaint, namely the sensation of pain in the joint area. Treatment for this disease is generally carried out in two ways, the first is pharmacological and the second is non-pharmacological. In nursing, non-pharmacological pain management can be done with certain techniques, such as distraction techniques and relaxation techniques. The use of red ginger as an alternative to pain management has begun to be widely practiced, such as for gout pain, gout arthritis pain, osteoarthritis pain and other joint pain whose cause is still unknown. The purpose of this study was to determine the effectiveness of red ginger compresses on the intensity of joint pain in patients with rheumatoid arthritis. The method used was one group pre test post test design, the research sample was 30 rheumatoid arthritis sufferers, data analysis used the Wilcoxone test. This research was carried out in April - May 2023 at the village of Jejawi District, Ogan Komering Ilir Regency. The results showed that the p value was 0.004. Based on these results, it was concluded that there was effectiveness of giving red ginger compresses weighing 30 grams dissolved in 500 ml of water and compressed for 1 hour on the intensity of joint pain in patients with rheumatoid arthritis.